“NEČISTA KRV“ AS ONTOLOGICAL OCCUPATION AND CENTURIES BORA’S GEN (Heritage, 2022)
Interpretation of a century’s duration of Bora Stanković’s “Nečista krv“, which has been approved by many researchers and interpreters, will be the main interest of this work. During the Scientific Conference in Vranje, regarding the 100th anniversary of its publishing, and the accompanying thematic collection, special attention will be paid to observing the novel and its author. This is not just a pure memory and necessary evocation to human’s drama, it is a reality which, through time distance, literary, esthetic and other disciplines brings closer the secret of multidimensional understanding, reading and interpreting of the phenomenon of “impure blood“.This overcomes one-sited attitude of the cause of tragic, it is a perception of the gene of Vranje, ontological and meaning of the work.Other elements and aspirations and being supplemented, refuted and produced through a prism of national culture and identity, which lead to its bard Bora Stanković and Vranje of his time.
Keywords: Bora Stanković, novel “Nečista krv“, interpretation, gen of Vranje, drama hero